A questionnaire survey of cervical and breast cancer screening among female employees and employees’ spouses - Asami Yagi; Yutaka Ueda; Sayaka Ikeda; Emiko Oka; Satoshi Nakagawa; Kosuke Hiramatsu; Kumi Komori; Rie Ozaki; Naomi Yutani; Saki Kanamoto; Yuki Taniguchi (Scientific Reports)
Abstract In Japan, cancer screening is conducted under a variety of umbrellas, i.e., via population-based screening, occupational health checkups, insured medical care, and personal medical checkups. Quality control assessment of cancer screenings is conducted by national and local governments only for population-based screenings. The purpose of this study was to clarify the status of women receiving cervical and breast cancer screenings in Japan by any of these means. As a model associated with occupational screenings, we surveyed female employees and male employees’ spouses of Sunstar, Inc., a Japanese subsidiary of an international corporation. The number of valid responses collected from March to July 2023 was 345. Among those who had cancer screening either regularly or irregularly, 66% (89/134) and 56% (47/84), respectively, received cervical and breast cancer screenings more frequently than every two years, the prescribed interval for population-based screening. Our survey revealed that a small number of women are routinely receiving cervical and breast cancer screenings more frequently than appropriate, suggesting a need to provide better information to screening consumers and providers on what constitutes appropriate screening schedules. Our survey also revealed that there is no governmental management entity for opportunistic screenings, so the status among female employees and male employee’s spouses of a company, Sunstar, Inc. is unclear.